Kitāb Sukkardān As-Sulṭān. - Sihāb ad-Dīn Aḥmad b. Yaḥyā b. Abī Bakr as-Sahīr bi-Ibn Abī Ḥaǧala al-Maġribi at-Tilmsānī, Sihāb ad-Dīn. (Bibliotheca Islamica Series, 2022)
Bibliotheca Islamica (BI) is the Orient-Institut Beirut's platform for the critical edition of mainly Arabic texts. The series dates back to 1929, when Hellmut Ritter edited the Kitāb Maqālat al-islamīyīn wa-ḫtilāf al-muṣallīn of Abū l-Ḥasan ʿAlī al-Asʿarī, a seminal text on dogmatic positions in the early Islamic period. Since then, the OIB has published more than fifty titles in this series.